Real-world efficacy and safety of nivolumab in previously-treated metastatic renal cell carcinoma, and association between immune-related adverse events and survival: the Italian expanded access program - Elena Verzoni; Giacomo Cartenì; Enrico Cortesi; Diana Giannarelli; Andrea De Giglio; Roberto Sabbatini; Sebastiano Buti; Sabrina Rossetti; Francesco Cognetti; Francesca Rastelli; Alberto Sobrero; Daniele Turci; et al. (Journal for ImmunoTherapy of Cancer, 2019)
Abstract Background The Italian Renal Cell Cancer Early Access Program was an expanded access program that allowed access to nivolumab, for patients (pts) with metastatic renal cell carcinoma (mRCC) prior to regulatory approval. Methods Pts with previously treated advanced or mRCC were eligible to receive nivolumab 3 mg/kg every 2 weeks. Pts included in the analysis had received ≥1 dose of nivolumab and were monitored for drug-related adverse events (drAEs) using CTCAE v.4.0. Immune-related (ir) AEs were defined as AEs displaying a certain, likely or possible correlation with immunotherapy (cutaneous, endocrine, hepatic, gastro-intestinal and pulmonary). The association between overall survival (OS) and irAEs was assessed, and associations between variables were evaluated with a logistic regression model. Results A total of 389 pts were enrolled between July 2015 and April 2016. Overall, the objective response rate was 23.1%. At a median follow-up of 12 months, the median progression-free survival was 4.5 months (95% CI 3.7–6.2) and the 12-month overall survival rate was 63%. Any grade and grade 3–4 drAEs were reported in 124 (32%) and 27 (7%) of pts, respectively, and there were no treatment-related deaths. Any grade irAEs occurred in 76 (20%) of patients, 8% cutaneous, 4% endocrine, 2% hepatic, 5% gastro-intestinal and 1% pulmonary. Of the 22 drAEs inducing treatment discontinuation, 10 (45%) were irAEs. Pts with drAEs had a significantly longer survival than those without drAEs (median OS 22.5 versus 16.4 months, p = 0.01). Pts with irAEs versus without irAEs had a more significant survival benefit (median OS not reached versus 16.8 months, p = 0.002), confirmed at the landmark analysis at 6 weeks. The occurrence of irAEs displayed a strong association with OS in univariable (HR 0.48, p = 0.003) and multivariable (HR 0.57, p = 0.02) analysis. Conclusions The appearance of irAEs strongly correlates with survival benefit in a real-life population of mRCC pts treated with nivolumab.